Evaluation of Economic Feasibility by Using ETLE in Increasing Road User Compliance to Reduce Traffic Accident Rates - Syahara Almas Safana (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
This study aims to evaluate the effectiveness, efficiency, and economic benefits of implementing the Electronic Traffic Law Enforcement (ETLE) system in Indonesia, particularly within the context of digital transformation in traffic law enforcement. Using a quantitative approach based on survey instruments, the research model was developed through the integration of Benefit-Cost. Four key variables were examined: the quality of ETLE camera installation, operational efficiency, road user compliance, and supporting implementation factors. The survey instrument was comprehensively constructed and validated through expert judgment, involving both academics and ETLE practitioners. Data were collected from 115 respondents through both online and offline distribution methods, targeting road users and ETLE system administrators. The results of the analysis indicate that all variables significantly influence traffic law compliance. Operational efficiency was found to be a key mediating factor between installation quality and user compliance. Furthermore, the Benefit-Cost Analysis revealed a BCR value of 3.01, indicating that every Rp1 invested in the ETLE system yields a social and economic return of 3.01. This study asserts that the ETLE system not only enhances the accountability and efficiency of law enforcement but also significantly reduces potential state losses resulting from traffic violations and accidents. The practical implications of these findings provide a strong foundation for formulating sustainable digital transportation policies.